Should Chopart Amputation be Performed in Diabetic Foot Ulcer Patients? - James D. Brodell; Judith F. Baumhauer MD, MPH; Benefict F. DiGiovanni MD; A. Samuel Flemister MD; John P. Ketz MD; Irvin Oh MD (Foot & Ankle Orthopaedics, 2019)
Category: Diabetes, Midfoot/Forefoot Introduction/Purpose: Diabetic foot ulcers (DFU) with deep infections and osteomyelitis often lead to partial or complete limb loss. Determination of the appropriate level for amputation is challenging, and is a complex decision based on the patient’s function at baseline, extent of infection, vascular patency and comorbidities. Although Chopart amputation preserves greater limb length than Syme amputation, additional procedures, such as Achilles tenectomy and tendon transfers are necessary to optimize residual foot function. Challenges with wound healing and prosthesis fitting have been reported. We aimed to investigate the functional and clinical outcomes including patient reported outcomes of Chopart and Syme amputations. Methods: A query utilizing current procedural terminology (CPT) codes was performed to identify patients who had undergone Syme or Chopart amputations for diabetic foot infections by an academic orthopaedic group between August 2013 and September 2018. Twenty-two patients with average age of 59.8 (range, 28-79) years, comprising 18 Chopart amputations and 4 Syme amputations were identified. Demographic characteristics, body mass index, hemoglobin A1c, medical comorbidities, major and minor post-operative complications, unplanned admission or return to OR, revision surgeries, and time to receiving a brace or prosthesis information were compiled. After informed consent was obtained, subjects completed three Patient-Reported Outcomes Measurement Information Systems (PROMIS) instruments (Pain Interference (PI), Physical Function (PF), and Depression), and the SF-36. Unpaired student t-tests and Fisher’s exact test were utilized to compare patient cohorts. Statistical analysis was performed using Stata®. Results: The majority (17/18) of Chopart and half (2/4) of Syme patients developed complications including wound dehiscence and recurrent/persistent infection. Readmission and unexpected return to the OR for irrigation and debridement or revision occurred in 11/18 (61%) of Chopart and 2/4 (50%) of Syme patients. Revision amputations occurred in 10/18 (56%) Chopart patients (2 Syme, 8 BKA), and 1/4 (25%) Syme patients (BKA). Half of Chopart patients never received a prosthesis due to delayed wound healing and revision amputation. All Syme amputation patients received a prosthesis and resumed ambulation. The average time to prosthesis was 4.5 and 6.5 months for Syme and Chopart patients, respectively. There was no significant difference between Syme and Chopart patients in all PROMIS domains, or the SF-36 (p-values > 0.05) (Table 1). Conclusion: We found a high rate of complications and revision procedures in Chopart amputation patients. In our patient cohort, there was a high likelihood that a patient who underwent a Chopart amputation ultimately received a below knee amputation. Even after wound healing, patients with Chopart amputations may struggle with obtaining a prosthesis suitable for ambulation. Syme amputation patients were less likely to require revision amputation, and received a prosthesis more rapidly relative to Chopart amputation patients. The complication and revision rates of Chopart amputations indicate that surgeons should exercise judicious patient selection prior to performing these procedures.